2009
DOI: 10.1007/s00330-009-1511-6
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labelling at 3-T MR imaging for detection of individuals with Alzheimer’s disease

Abstract: The purpose of this study was to determine whether arterial spin labelling (ASL) at 3-T MR imaging can be used to discriminate individuals with Alzheimer's disease (AD) from cognitively normal subjects. Twenty AD patients and 23 cognitively normal control subjects were studied using ASL on a 3-T MR imager. Absolute regional cerebral blood flow (rCBF) maps were calculated. In addition, normalized rCBF maps were obtained using CBF in the sensorimotor cortex for normalization. A voxel-wise comparison of these rCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…Alzheimer's disease, where reduction in gray matter CBF, thought to be secondary to neuroaxonal loss from neurodegeneration, is not accompanied by alteration in BAT. 20,22 As prolongation of BAT represents reduction in arterial flow velocity, prolonged BAT in deep gray matter could indicate CBF was reduced without commensurate reduction in arterial Significance assessed using regression with co-variates of age, gender, and brain parenchymal fraction. Bold values are significant at Po0.05.…”
Section: Increased Cerebral Blood Flow and Prolonged Bolus Arrival Timentioning
confidence: 99%
“…Alzheimer's disease, where reduction in gray matter CBF, thought to be secondary to neuroaxonal loss from neurodegeneration, is not accompanied by alteration in BAT. 20,22 As prolongation of BAT represents reduction in arterial flow velocity, prolonged BAT in deep gray matter could indicate CBF was reduced without commensurate reduction in arterial Significance assessed using regression with co-variates of age, gender, and brain parenchymal fraction. Bold values are significant at Po0.05.…”
Section: Increased Cerebral Blood Flow and Prolonged Bolus Arrival Timentioning
confidence: 99%
“…8 ASL is increasingly recognized as a noninvasive method for quantitative CBF measurement for assessing stroke, neurodegenerative diseases, and brain tumors. [8][9][10][11][12][13][14] ADC measurement is a widely used method.…”
mentioning
confidence: 99%
“…12 A more recent study indicated that CBF maps obtained with 3D ASL can be a marker for disease severity ranging from mild cognitive impairment to advanced AD. 13 Although many recent ASL perfusion studies were performed on 3T MR imaging, it has been shown in other studies that ASL with 1.5T MR imaging could detect regional hypoperfusion, mainly in the temporoparietal association cortex and the posterior cingulate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Many AD studies by use of ASL have been reported, which indicates that ASL MR imaging is an indispensable technique for studying AD. [8][9][10][11][12] CBF measured with ASL MR imaging can detect regional hypoperfusion in the AD precuneus and bilateral parietal cortex and discriminate individuals with AD from normal subjects. Recent research with the use of pulsed-continuous reported that 3D ASL can evaluate the severity of cognitive impairment as measured by the correlation of CBF with cognition.…”
mentioning
confidence: 99%